Atomicity and isolation for transactional processes. - Schuldt, Heiko; Alonso, Gustavo; Beeri, Catriel; Schek, Hans-Jörg.
Processes are increasingly being used to make complex application logic explicit. Programming using processes has significant advantages but it poses a difficult problem from the system point of view in that the interactions between processes cannot be controlled using conventional techniques. In terms of recovery, the steps of a process are different from operations within a transaction. Each one has its own termination semantics and there are dependencies among the different steps. Regarding concurrency control, the flow of control of a process is more complex than in a flat transaction. A process may, for example, partially roll back its execution or may follow one of several alternatives. In this article, we deal with the problem of atomicity and isolation in the context of processes. We propose a unified model for concurrency control and recovery for processes and show how this model can be implemented in practice, thereby providing a complete framework for developing middleware applications using processes.
Keywords: Advanced transaction models; Business process management; Electronic commerce; Execution quarantees; Locking; Rocesses; Semantically rich transactions; Transactional workflows; Unified theory of concurrency control and recovery